Synchronization of the unified chaotic system and application in secure communication - Grzybowski, J. M. V.; Rafikov, M.; Balthazar, José Manoel [UNESP] (Elsevier B.V., 2009)
This paper Studies the synchronization of the unified chaotic system via optimal linear feedback control and the potential Use of chaos in cryptography, through the presentation of a chaos-based algorithm for encryption. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chaos; Synchronization; Communication